Aromatic Micelles as a New Class of Aqueous Molecular Flasks. Issue 66 (18th September 2017) - Kondo, Kei; Klosterman, Jeremy K.; Yoshizawa, Michito
Abstract: Micelles are a versatile class of molecular assemblies typically composed of aliphatic molecules with hydrophilic groups. Polyaromatic molecules with hydrophilic groups, on the other hand, usually do not assemble into micellar structures in water but rather form columnar, π‐stacked architectures. This Minireview article focuses on the recent development of aqueous micellar nanostructures with multiple oligoarylene rods or polyaromatic panels. The new micelles with spherical polyaromatic shells, which we name "aromatic micelles", serve as functional molecular flasks with superior binding abilities for medium to very large molecules in water. Abstract : Adaptable nanocontainers : Micelles are the oldest class of supramolecules and are typically composed of amphiphilic molecules with aliphatic subunits. This Minireview focuses on the recent development of micellar nanostructures formed from amphiphiles with oligoarylene or polyaromatic frameworks. The new aromatic micelles providing polyaromatic shells display superior binding capabilities toward medium to large molecules in water.